Effect of Exogenous Enzyme Supplementation on Haemato-biochemical Parameters and Antioxidant Status in Dual-type Laying Hens Fed Wheat Bran-based Diets - Raj, Aditya; Kumar, Kaushalendra; Kumar, Sanjay; Singh, Pankaj Kumar; Sinha, Ravi Ranjan Kumar; Kumar, Dharmendra; Koley, Sankhanath (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during March to August months in the year 2024 at Poultry Research and Training Centre, Bihar Animal Sciences University, Patna, India to evaluate the influence of phytase and xylanase supplementation on haemato-biochemical parameters and antioxidant status in Vanaraja laying hens. A total of 280 hens were randomly allocated to seven dietary groups, each consisting of 40 birds (five replicates of eight hens), study aimed to evaluate the effects of dietary supplementation of phytase, xylanase, and their combinations on haemato-biochemical parameters and serum antioxidant status in dual-purpose laying hens (Vanaraja) fed a wheat bran-based diet under farm conditions. The dietary treatments included: T1 (control, basal ration), T2 (basal ration+400FTU kg-1 phytase), T3 (basal ration+1200FTU kg-1 phytase), T4 (basal ration+1000XU kg-1 xylanase), T5 (basal ration+3000XU kg-1 xylanase), T6 (basal ration+400FTU kg-1 phytase+1000XU kg-1 xylanase), and T7 (basal ration+1200FTU kg-1 phytase+3000XU kg-1 xylanase). Birds received a fixed amount of feed and ad libitum access to water throughout the 24-week trial. Haematological parameters remained unaffected across all treatments. Serum biochemical indices, including total protein, albumin, AST, ALT, and ALP, showed no significant differences (p>0.05). Serum mineral concentrations were generally comparable, except for calcium and phosphorus levels, which significantly increased (p<0.05) in enzyme-supplemented groups in a dose-dependent manner. Antioxidant indices were unaffected; however, GSH levels were significantly elevated (p<0.05) in certain enzyme-treated groups compared to the control. In conclusion, supplementation with phytase and xylanase, alone or in combination, proved beneficial without adverse effects on blood metabolites. However, higher enzyme inclusion beyond the optimal level did not confer additional benefits and may not be warranted in Vanaraja laying hens.